Women seed entrepreneurship: Key highlights - Kapur, Aman; Nayak, Prakash Kumar; Khan, Afreen; Puskur, Ranjitha (International Rice Research Institute, 2024)
WP6 of Seed Equal aims to enhance gender inclusivity and entrepreneurship within seed systems by addressing gender-specific barriers and promoting equitable seed access. IRRI leads efforts in conducting situational analyses, developing gender-transformative strategies, and capacity-building. Partner organizations (POs) include the: Access Livelihoods Foundation (ALF), Centre for Sustainable Agriculture (CSA), and Pragati. These POs are actively involved in Andhra Pradesh, Odisha, and Telangana working on seed production, marketing development, and community engagement.